Identification and genetic characterization of Sarcocystis arctica and Sarcocystis lutrae in red foxes (Vulpes vulpes) from Baltic States and Spain - Viktorija Kirillova; Petras Prakas; Rafael Calero-Bernal; Inese Gavarāne; José Luis Fernández-García; Manuel Martínez-González; Eglė Rudaitytė-Lukošienė; Miguel Ángel Habela Martínez-Estéllez; Dalius Butkauskas; Muza Kirjušina (Parasites & Vectors, 2018)
Abstract Background Typically, carnivores serve as definitive hosts for Sarcocystis spp. parasites; currently, their role as intermediate hosts is being elucidated. The present study aimed to identify and molecularly characterize Sarcocystis cysts detected in striated muscle of red foxes from different populations in Latvia, Lithuania and Spain. Methods Muscle samples from 411 red foxes (Vulpes vulpes) and 269 racoon dogs (Nyctereutes procyonoides) from Latvia, 41 red foxes from Lithuania and 22 red foxes from Spain were examined for the presence of Sarcocystis sarcocysts by light microscopy (LM). Sarcocystis spp. were identified by transmission electron microscopy (TEM) and molecular biology techniques. Results Sarcocystis cysts were detected in 11/411 (2.7%) Latvian, 3/41 (7.3%) Lithuanian, and 6/22 (27.3%) Spanish red foxes, however, cysts were not observed in the muscles of racoon dogs. Based on LM, TEM, 18S rDNA, 28S rDNA, ITS1, cox1 and rpoB sequences, Sarcocystis arctica and Sarcocystis lutrae cysts were identified in red fox muscles from Latvia and Lithuania, whereas only S. arctica was detected in Spain. The 18S rDNA, 28S rDNA and ITS1 sequences from the 21 isolates of S. arctica from Latvia, Lithuania and Spain were identical. By contrast, two and four haplotypes were determined based on mtDNA cox1 and apicoplast rpoB sequences, respectively. Polymorphisms were not detected between the two isolates of S. lutrae from Latvia and Lithuania. Based on phylogenetic results, S. arctica and S. lutrae were most closely related to Sarcocystis spp. using predatory mammals as intermediate hosts and to Sarcocystis species with a bird-bird life-cycle. Conclusions Based on current knowledge, the red fox and Arctic fox (Vulpes lagopus) could act as intermediate host for the same two Sarcocystis species. Molecular results suggest the existence of two genetic lineages of S. arctica, and such divergence relies on its geographical distribution but not on their intermediate host species.